Systems change: A guide to what it is and how to do it (Ellen Harries, 2015)
Systems change has been attracting the attention of those in the social sector who want to deal with the root causes of problems, but, despite the buzz, much of what is written is abstract in tone. With the support of LankellyChase Foundation we have produced this guide to plug a gap in the systems change literature—providing accessible material and recommendations for action. Systems change has been attracting the attention of a range of progressive charities, funders and practitioners who are interested in dealing with the root causes of social problems. But while there is a buzz about a subject relatively new to the social sector, it is easy to feel frustrated by the literature—much of what is written is abstract in tone and there are few examples of success. We have produced this paper to address this problem and offer accessible material and recommendations for action. This systems change guide: Clarifies what is meant by systems and systems change Describes the main perspectives on systems change Outlines good practice for systems change Identifies what is and is not agreed upon by experts in the field Provides recommendations for charities, funders and the public sector on how to act systemically. We hope this presents a manageable introduction to the systems change field, especially for those new to it, and also guides those interested in acting systemically to improve the lives of people in need. Our conclusion is that although it may not be as novel as some claim, there is a good deal of value in a systems change approach and it offers a welcome reminder of what effective action looks like when it comes to the pursuit of social change.